Serum neurofilament light chain in myasthenia gravis subgroups: An exploratory cohort and case–Control study - Stascheit, Frauke; Aigner, Annette; Mergenthaler, Philipp; Hotter, Benjamin; Hoffmann, Sarah; Lehnerer, Sophie; Meisel, Christian; Meisel, Andreas (Frontiers in Neurology, 2023)
Background: To evaluate the association of neurofilament light chain (Nfl) with neuromuscular destruction and disease severity in serum of patients with myasthenia gravis (MG). Materials and Methods: Sera from 134 patients with MG with varying degree of disease severity and autoantibody (Abs) status were analyzed and compared to controls in a cross-sectional design. Prospectively, we additionally measured serum NfL (sNfl) levels in MG patients longitudinally up to 3 years. Based on linear regression differences between patients and controls were assessed. With correlation coefficients and mixed linear regression the association between sNfl levels, socio-demographics, disease activity (Quantitative Myasthenia Gravis (QMG) score, Myasthenia Gravis Activities of Daily Living (MG-ADL) scale), Abs-status (acetylcholine receptor antibody (AChR-Abs), muscle specific receptor tyrosine kinase antibody (MuSK-Abs), lipoprotein-related protein 4 (LRP4), seronegative), Abs titer, treatment regime (pyridostigmine, steroids, immunosuppressive therapies), and thymectomy were investigated. Results: sNfl levels were higher in MG patients compared to controls (median: 11.2 vs 7.88), where sNfl levels were highest in anti-AChR-Abs positive patients (median 12.6), followed by anti-MuSK-Abs positive, anti-LRP4-Abs positive and seronegative patients. Adjusting for age and sex, MG patients’ sNfl levels were on average 35% higher compared to controls (35.1, 95% CI: 8.4;68.3) and highest for seronegative MG patients (44.35; 95% CI 16.47; 78.90). We found no relevant relationship between individual changes of sNfl with changes in QMG and MG-ADL scores. Conclusions: sNfl levels are higher in MG patients than in controls but was not consistently associated with clinical severity. Thus, sNfl is not a suitable biomarker to monitor individual disease progression in MG patients.